1999
DOI: 10.1159/000012786
|View full text |Cite
|
Sign up to set email alerts
|

EPIC-Germany – A Source for Studies into Diet and Risk of Chronic Diseases

Abstract: The ‘European Investigation into Cancer and Nutrition (EPIC)’ represents one of the main scientific activities of the EU program ‘Europe against Cancer’ and is a large-scale cohort study on diet and chronic diseases, especially cancer, with approximately 475,000 study participants. The German contribution amounted to 53,000 study participants recruited between 1994 and 1998. The study instruments of the baseline examination included self-administered questionnaires for optical reading, PC-guided interviews, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
205
0
10

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(217 citation statements)
references
References 18 publications
(22 reference statements)
0
205
0
10
Order By: Relevance
“…The EPIC-Potsdam Study 30 represents one study centre of the European multi-centre, prospective cohort study EPIC. 31 Baseline recruitment in Potsdam, Germany, started in 1994 and ended in 1998.…”
Section: Methodsmentioning
confidence: 99%
“…The EPIC-Potsdam Study 30 represents one study centre of the European multi-centre, prospective cohort study EPIC. 31 Baseline recruitment in Potsdam, Germany, started in 1994 and ended in 1998.…”
Section: Methodsmentioning
confidence: 99%
“…However, validation studies have shown that self-reported data on colonoscopy are very dependable (Baier et al, 2000;Hall et al, 2004;Hoffmeister et al, 2007). Third, as only 38.5% of individuals originally invited (random population sample) had agreed to participate in the EPIC study, the studied cohort is a selfselected subgroup of the underlying population (Boeing et al, 1999a(Boeing et al, , 1999b. As previous investigations have shown that the educational level of the EPICHeidelberg population is higher than that of the reference population, selection bias can be assumed.…”
Section: Limitationsmentioning
confidence: 99%
“…As previous investigations have shown that the educational level of the EPICHeidelberg population is higher than that of the reference population, selection bias can be assumed. However, this selective participation does not prevent etiological conclusions as associations are derived internally as the relative risk (Boeing et al, 1999a(Boeing et al, , 1999b. In the analyses presented here, only individuals who completed all three questions on colonoscopy utilization (n = 15 014) were included.…”
Section: Limitationsmentioning
confidence: 99%
“…Baseline examinations comprised a self-administered food frequency questionnaire (FFQ), a computer-guided interview on lifestyle habits and medical history, and anthropometric measurements performed by trained staff. Every 2-3 years, the participants received a mailed follow-up questionnaire to assess incident diseases (Bergmann et al, 1999;Boeing et al, 1999b). Response rates for each follow-up round were between 93 and 96%.…”
Section: Study Populationmentioning
confidence: 99%